Estado de salud bucodental y sus determinantes en la población escolar de dos distritos de Poás, 2010 - Campos Arias, Flor de María (2014)
This study refers to research on oral health and its determinants in students at schools Monsignor Luis Rodríguez Salas and Delfin Quesada, district of San Rafael and Sabana Redonda in the canton of San Pedro de Poas, Province Alajuela, Costa Rica. The sample was 127 students, 2, 4 and 6, who were assessed health status and hygiene. Parents of children they spent a sociodemographic questionnaire of 55 questions, which also included information on food hygiene and among the findings highlighted the educational level of parents: 75% of parents with higher education rated the importance of primary teeth compared with 40% of parents with no formal education who do not think so. Fruit consumption is associated with a higher educational level of parents, with a statistically significant difference (p = 0.023) in direct proportion, both variables There is also a direct relationship between the frequency of visits to the dentist and brushing with the educational level of parents. The more information parents received dental care, just as did their children. 58% of parents always or almost always deal with the review of the dental cleaning of their children. 58% of parents say they visit the dentist often. It is emphasized, that the higher the educational level of mother, and father, the higher the percentage of people who frequently attend the dentist. As educational level increases both father and mother, less time that has elapsed since the last visit the dentist. 73% of children have the piece number 46 healthy, as higher the educational level of parents, higher percentage of children with the pieces number 46 healthy. It was found that with advancing age of the child decreases the prevalence of this healthy piece. Similarly, the highest percentage of children with healthy 4.6 part were the children of parents with more formal education. Therefore, education was the variable that had a higher positive correlation with positive aspects of the health status of schoolchildren. This factor is closely associated to the example of parents to children within the family, the foundation of society. Hence the importance of using parent-child pairing patterns to build hygiene and nutrition for a healthier population